Actuation concepts for adaptive high-rise structures subjected to static wind loading. (15th September 2022) - Steffen, Simon; Zeller, Amelie; Böhm, Michael; Sawodny, Oliver; Blandini, Lucio; Sobek, Werner
Highlights: Adaptive high-rise structures enable structural material savings. The primary control objective should be deformation control. The actuation concept can be derived from the passive load-bearing behavior. The derivation can be done using actuation influence matrices. Certain structural topologies enable a stress-free deformation control. Abstract: High-rise structures can efficiently provide living space in urban areas with high density population since they require a comparatively smaller footprint than low-rise structures. This aspect is important particularly considering world population growth and urbanization trends. However, the structural mass required for high-rise structures increases nonlinearly as the structure becomes taller and more slender to the extent that resource and emission efficiency decrease compared to low-rise structures. In the context of climate change and impending resource scarcity, new material and emission efficient building technologies must be developed. One such approach are adaptive load-bearing structures, i.e., structures that can adapt and optimize their load-bearing behaviour under changing loading conditions. This paper studies the adaptability of two idealised high-rise structures to static lateral loads by means of actuation influence matrices. The high-rise structures are assembled from basic bracing modules of a truss and frame. A reduction of deformations is proposed as primary control objective and two actuation concepts are derived from the passive load-bearing behaviour of the high-rises. The actuation concept for truss structures achieves a stress-free deformation control.